'Storylistening' as a methodology for peacebuilding among young survivors of conflict and their communities in Colombia. Issue 1 (March 2023) - Charles, Mathew H; Fowler-Watt, Karen
Working on a participatory arts project with former child soldiers and young survivors of conflict in Colombia's indigenous Nasa community led to the development of an alternative to the qualitative interview, which we call 'story listening '. Storylistening is a methodology for peacebuilding that took shape within a narrative based culture and embraces the importance of acknowledging the everyday, as perceived and lived by young indigenous people. Within the context of conflict and reintegrating former child soldiers, storylistening emerged from a strong oral storytelling tradition to offer a dynamic and local approach to peacebuilding. This methodology shaped the production of an animated documentary, El árbol del amor (The Tree of Love), which explores the world of forced recruitment and child soldiering. The storylistening concept contains elements of auto/biography, in that it engages with memory and identity, where space and time are important. Based on Durkheimian notions of the socioemotional, storylistening shows how sharing emotions contributes to creating, maintaining and strengthening social bonds that can inspire change. It is an active process and has a shared impact on the 'listener' and the 'teller', whereas storytelling is an individual process that does not always carry the guarantee of being listened to. For the individual, storylistening offers the potential of catharsis, while for the community, it offers the opportunity for collective reflection. In the particular case of former child soldiers, storylistening engenders effective reintegration and more broadly fosters reconciliation, which underpins peacebuilding at the community level.